Turkish durum wheat conserved ex‐situ and in situ unveils a new hotspot of unexplored genetic diversity. Issue 3 (28th March 2022) - Alsaleh, Ahmad; Bektas, Harun; Baloch, Faheem Shehzad; Nadeem, Muhammad Azhar; Özkan, Hakan
Abstract: Durum wheat ( Triticum turgidum L.) is the 10 th most cultivated crop and is a vital food source for human consumption. Genetic diversity in durum wheat is still an unexplored subject, and gene banks are filled with accessions waiting to be screened. Here, four different groups of durum wheat, Turkish and foreign cultivars, and in situ and ex situ landraces were evaluated for population structure and genetic diversity. A collection of 129 durum wheat accessions were genotyped, with a total of 6, 357 markers (SilicoDArT, SNP [single‐nucleotide polymorphism], and simple sequence repeats [SSRs]). The highest mean allele number per marker (1.562) was obtained with SNP markers in ex situ landraces; the lowest mean allele number per marker (0.788) was obtained with SSR markers in the foreign cultivars. The minimum percentage of polymorphic loci was 38.70% observed with SSR markers in foreign cultivars; the maximum was 76.20% in SilicoDArT markers in ex situ landraces. According to Neighbor‐Joining analyses, the studied collection was divided into groups of cultivars and landraces, with some level of admixtures. Structure and principal coordinate analysis obtained distinct clusters for ex situ landraces and foreign cultivars, supported by Neighbor‐Joining analysis. A significant level of intergroup and intragroup variation was observed, and Turkish ex situ landraces were found as the most diverse and distinct group in the collection. Turkish landraces may be a promising source of novel allelic diversity that can be used in durum wheat breeding worldwide. Core Ideas: Turkish durum wheat landraces may provide novel allelic diversity. Turkish durum wheat cultivars released in the late 20 th century has close pedigree relations with foreign cultivars. Turkish modern wheat germplasm/gene pool have experienced a bottleneck for several reasons. Turkish cultivars divide into two distinct groups: foreign related and landrace related.